Therapeutic Relationships in Aphasia Rehabilitation: Using Sociological Theories to Promote Critical Reflexivity - Bright, Felicity; Hersh, D; Attrill, S (Wiley, 2020)
Background Therapeutic relationships are fundamental in aphasia rehabilitation, influencing patient experience and outcomes. While we have good understandings of the components of therapeutic relationships, there has been little exploration of how and why therapists construct and enact relationships as they do. Sociological theories may help develop nuanced understanding of the values, assumptions and structures that influence practice, and may facilitate critical reflexivity on practice. Aims To explore the potential for theoretical approaches from outside speech–language therapy to enable a deeper understanding of the nature and enactment of therapeutic relationships in aphasia rehabilitation. Methods & Procedures An explanatory single case study of one speech–language therapist–patient dyad in an in‐patient stroke rehabilitation setting. Data included observations of five interactions, two interviews with the client and three interviews with the speech–language therapist. Analysis was guided by analytical pluralism that applied aspects of three sociological theories to guide data analysis and make visible the contextual factors that surround, shape and permeate the enactment of therapeutic relationships. Outcomes & Results The analysis of this dyad made visible individual, interactional and broader structural features that illustrate the dynamic processes that practitioners and patients undertake to enact therapeutic relationships. Clinical practice could be viewed as a performance with each person continually negotiating how they convey different impressions to others, which shapes what work is valued and foregrounded. The patient and therapist took up or were placed in different positions within the interactions, each with associated expectations and rights, which influenced what types of relationships could, or were likely to, develop. Organizational, rehabilitation and individual practitioner structures assigned rules and boundaries that shaped how the therapist developed and enacted the therapeutic relationship. Whilst the therapist had some agency in her work and could resist the different influencing factors, such resistance was constrained because these structures had become highly internalized and routinized and was not always visible to the therapist. Conclusions & Implications While therapists commonly value therapeutic relationships, social and structural factors consciously and unconsciously influence their ability to prioritize relational work. Sociological theories can provide new lenses on our practice that can assist therapists to be critically reflexive about practice, and to enact changes to how they work to enhance therapeutic relationships with clients.
Keywords: Therapeutic relationships; Aphasia; Rehabilitation; Sociology; Theory; Critical reflexivity